Time to exhaustion at 90 and 100% VO2max and physiological determinants of 3 km performance in elite cyclists - Zacharogiannis, E.; Pilianidis, T.; Dallas, G.; Mantzuranis, N.; Argitaki, P.; Smirniotou, A.; Paradisis, G. (European Journal of Physical Education and Sport Science, 2021)
The minimal power that elicits VO2max and the time to exhaustion (tlimit) at this workload appear to determine cyclists` endurance capabilities, analyze performance and help coaches to design training. Data in the literature are limited so as to elucidate this. The aim of this study was to investigate the tlimit at the power output, which corresponds to 90 (tlimit 90) and 100% VO2max (tlimit 100) in elite endurance cyclists. The contribution of tlimit in 3 km indoor individual time trial was also studied. Subjects were eleven elite male road cyclists (age 17.7 +/- 0.5 years, body mass 66.8 +/- 4.9 kg, body height 176.3 +/- 7.4 cm, VO2max 69.77 +/- 2.58 ml.kg-1.min-1). Power output at 90 and 100% VO2max was determined by continuous incremental testing. This protocol had steps of 2 min and increments of 30 W. The exhaustive trials tlimit 90 or tlimit 100 were performed in random order at least five days apart. Five days after the last exhaustive trial, cyclists performed an individual 3 km time trial on an indoor wooden track. Mean +/-sd, tlimit 90 and tlimit 100 were 16:27.73 +/- 07:46.6 and 4:48.6 +/i 00:53.2 min:sec. Time to exhaustion at tlimit 90 and tlimit 100 ranged between 07:00-30:15 and 03:10-06:00 min:sec, respectively. Tlimit 100, tlimit 90 and VO2max (ml.min-1) did not correlate with 3 km cycling performance (r = 0.08, 0.16 and -0.59, p > 0.05). Tlimit 90 was inversely related (r = -0.49, p = 0.1) with VO2max (ml.min-1). Only power output which corresponded to ventilatory threshold and VO2max correlated significantly with 3 km performance (r = -0.83 and -0.80, p < 0.01). The results of this study indicate that: a) if cyclists` training intensity is based on %VO2max, individual determination of the tlimit at the %VO2max has to be considered due to a wide range of tlimit to exhaustion; b) 3 km performance directly depends on the power that corresponds with ventilatory threshold and VO2max.